2002
DOI: 10.1038/sj.bjc.6600348
|View full text |Cite
|
Sign up to set email alerts
|

High activity Rhenium-186 HEDP with autologous peripheral blood stem cell rescue: a phase I study in progressive hormone refractory prostate cancer metastatic to bone

Abstract: We tested the feasibility and toxicity of high activities Rhenium-186 hydroxyethylidene diphosphonate, with peripheral blood stem cell rescue in patients with progressive hormone refractory prostate cancer metastatic to bone. Twenty-five patients received between 2500 and 5000 MBq of Rhenium-186 hydroxyethylidene diphosphonate followed 14 days later by the return of peripheral blood peripheral blood stem cells. Activity limiting toxicity was defined as grade III haematological toxicity, lasting at least 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The disadvantage of further activity escalation was dose-limiting myelosuppression. A subsequent phase I study demonstrated PSA reduction in CRPC patients treated with high-activity 186 Re-HEDP and peripheral stem cell support [41].…”
Section: Perspectivesmentioning
confidence: 99%
“…The disadvantage of further activity escalation was dose-limiting myelosuppression. A subsequent phase I study demonstrated PSA reduction in CRPC patients treated with high-activity 186 Re-HEDP and peripheral stem cell support [41].…”
Section: Perspectivesmentioning
confidence: 99%
“…The standard dose of 1,295 MBq is recommended as safe, even in heavily pretreated patients (13). However, some data support administering higher doses, which are more likely to reduce tumor markers, ablate micrometastasis, and bring about the disappearance of bony lesions (17). In addition, when there is extensive skeletal involvement, the calculated absorbed dose to specific metastatic deposits has been shown to be significantly reduced (18).…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that it is the reason that 186 Re-MAG3-HBP binds to the hydroxyapatite in bone and is retained for a long term without excretion. peripheral blood stem cell transplant [33,34], the strategy should be more effective. At the same time, the dose absorbed by red marrow, which is known as a dose-limiting factor of bone-seeking radiopharmaceuticals, was not decreased.…”
Section: Dosimetrymentioning
confidence: 99%